Reference Ranges for NT-proBNP (N-Terminal Pro-B-Type Natriuretic Peptide) and Risk Factors for Higher NT-proBNP Concentrations in a Large General Population Cohort. (13th September 2022) - Welsh, Paul; Campbell, Ross T.; Mooney, Leanne; Kimenai, Dorien M.; Hayward, Caroline; Campbell, Archie; Porteous, David; Mills, Nicholas L.; Lang, Ninian N.; Petrie, Mark C.; Januzzi, James L.; McMurray, John J.V.; et al.
Abstract : Background: Demographic differences in expected NT-proBNP (N-terminal pro-B-type natriuretic peptide) concentration are not well established. We aimed to establish reference ranges for NT-proBNP and explore the determinants of moderately elevated NT-proBNP under the universal definition of heart failure criteria. Methods: This is a cross-sectional study. NT-proBNP was measured in serum from 18 356 individuals without previous cardiovascular disease in the Generation Scotland Scottish Family Health Study. Age- and sex-stratified medians and 97.5th centiles were generated. Sex stratified risk factors for moderately elevated NT-proBNP (≥125 pg/mL) were investigated. Results: In males, median (97.5th centile) NT-proBNP concentration at age <30 years was 21 (104) pg/mL, rising to 38 (195) pg/ml at 50 to 59 years, and 281 (6792) pg/mL at ≥80 years. In females, median NT-proBNP at age <30 years was 51 (196) pg/mL, 66 (299) pg/mL at 50 to 59 years, and 240 (2704) pg/mL at ≥80 years. At age <30 years, 9.8% of females and 1.4% of males had elevated NT-proBNP, rising to 76.5% and 81.0%, respectively, at age ≥80 years. After adjusting for risk factors, an NT-proBNP ≥125 pg/mL was more common in females than males (OR, 9.48 [95% CI, 5.60–16.1]). Older age and smoking were more strongly associated with elevated NT-proBNP in males than in females ( P sex interaction <0.001, 0.07, respectively). Diabetes was inversely associated with odds of elevated NT-proBNP in females only ( P sex interaction =0.007). Conclusions: An NT-proBNP ≥125 pg/mL is common in females without classical cardiovascular risk factors as well as older people. If NT-proBNP becomes widely used for screening in the general population, interpretation of NT-proBNP levels will require that age and sex-specific thresholds are used to identify patients with potential pathophysiology.